Relation of mitral valve morphology to surgical repair results in patients with mitral valve prolapse: A three‐dimensional transesophageal echocardiography study. Issue 9 (19th June 2018) - Pardi, Mirian M.; Pomerantzeff, Pablo M. A.; Sampaio, Roney Orismar; Abduch, Maria C.; Brandão, Carlos M. A.; Mathias, Wilson; Grinberg, Max; Tarasoutchi, Flavio; Vieira, Marcelo L. C.
Abstract : Background: The identification of predictors of mitral valve (MV) repair results is important for quality improvement in cardiac surgery. The aim of this study was to evaluate the relationship between MV morphological quantification by three‐dimensional (3D) transesophageal echocardiography and mitral repair results. Methods: Fifty‐four patients with MV prolapse who were submitted to surgical repair were divided into 2 groups according to their postoperative mitral regurgitation (MR) degree (group 1, grade 0‐I MR; group 2, ≥grade II MR). Morphological parameters related to the mitral ring, dimension of leaflets and prolapse, coaptation line, distance from papillary muscles to the leaflet border and valve angles were analyzed by 3D MV quantification. Cardiac remodeling and MR quantitative parameters were also evaluated. Results: There was no correlation between 3D MV quantification and surgical results; a multivariate analysis did not show an association between morphological parameters and surgical outcome. The distance from the posteromedial papillary muscle to the leaflet border was higher ( P  = .038) in patients with ≥grade II postoperative MR. The left atrial diameter, left ventricular end‐systolic diameter, left ventricular end‐diastolic and end‐systolic volumes were larger in patients with a significant residual MR ( P  < .05). Conclusion: Three‐dimensional MV quantification did not predict the postoperative MR grade; however, the distance from the posteromedial papillary muscles to the leaflet border may be related to suboptimal repair results. Furthermore, excessive cardiac remodeling was related to postoperative MR ≥ grade II, what could suggest a potential benefit of early surgical treatment.